SKRINING ANEMIA ANAK, PENYAKIT DEGENERATIF PENGURUS DAN EDUKASI KESEHATAN DI PANTI ASUHAN GENERASI PENGUBAH - Setianingrum, Elisabeth Levina Sari; Lada, Christina Olly; Rini, Desi Indria; Syahrir, Syahrir (Universitas Nusa Cendana, 2025)
Nutritional problems such as stunting and anemia in children, as well as the increasing prevalence of degenerative diseases among the productive-age population, remain major public health challenges in Indonesia. Children living in orphanages are at higher risk of nutritional problems due to limited access to balanced meals, lack of health education, and suboptimal living conditions. This community service program aimed to screen for stunting and anemia among children and to detect early risk factors for degenerative diseases among orphanage caregivers. The partner of this activity was Panti Asuhan Generasi Pengubah Kupang, which accommodates children from underprivileged families. The methods included anthropometric measurements, hemoglobin and hematocrit assessments and lipid profile and blood glucose examinations. Additionally, health education sessions were conducted on anemia, stunting, and metabolic syndrome using educational posters and interactive discussions. The results showed that 60.4% of respondents experienced anemia, predominantly mild anemia, and several children were identified as being at risk of stunting. Lipid profile and blood glucose screening among caregivers revealed elevated cholesterol and triglyceride levels in two respondents, indicating a high risk of cardiovascular disease and prediabetes. The health education sessions improved participants’ knowledge regarding balanced nutrition, physical activity, and the importance of regular health check-ups. This program successfully enhanced health awareness, improved caregivers’ skills in independent health monitoring, and strengthened collaboration with local primary health care centers for follow-up and routine monitoring.